PENERAPAN HUKUM PELAKU TINDAK PIDANA ZINA KHALWAT DI NAGROE ACEH DARUSSALAM DALAM PASAL 23 NOMOR 6 TAHUN 2014 TENTANG HUKUM JINAYAT - Khaerunnisa, Syifa Mega; Winda Widya Sari; Deden Najmudin (Cahaya Ilmu Bangsa Institute, 2024)
Seclusion is an act that is close to adultery, the Islamic religion strictly forbids its followers from committing adultery. Therefore khalwat is a criminal act/jarimah which can be subject to ta'zir sanctions, this is because khalwat can lead a person to commit adultery or have relations with a husband and wife outside of legal marriage. the crime of adultery and seclusion based on Article 23 Number 6 of 2014 concerning Jinayat Law. Referring to the Aceh Qanun Jinayat, the resolution of khalwat cases can be summarized into two types by looking at the perspective of the perpetrator, namely by resolving khalwat through the Syar'iyyah Court and resolving khalwat through the Customary Courts.